Network games, peer effect and neutral transfers - Dike Chukwudi Henry (University of Kent, School of Economics, 2021)
We study properties of collective action problems bounded by minimal contributions as well as endowment and variable contributions are neighbourhood dependent. We relate nearness to non-interior agents and its implication for interior contribution. Here, we see the aspects of node distance to non-interior agents which have implications for interior agents. Endowments may be redistributed among agents. We highlight strict conditions for budget-balanced transfers for which neighbourhood contributions and individual residual consumption are invariant. Agents may or may not be concerned about neighbourhood outcomes. We find that welfare is self-correcting and neither cases are relevant to the overall welfare impact of neutral transfers.
Keywords: C72; D85; H41; 330; Centrality; Contagion; Neutrality; Peer Effect